Smoking increases risk of pain chronification through shared corticostriatal circuitry. Issue 2 (12th October 2014) - Petre, Bogdan; Torbey, Souraya; Griffith, James W.; De Oliveira, Gildasio; Herrmann, Kristine; Mansour, Ali; Baria, Alex T.; Baliki, Marwan N.; Schnitzer, Thomas J.; Apkarian, Apkar Vania
Abstract Smoking is associated with increased incidence of chronic pain. However, the evidence is cross‐sectional in nature, and underlying mechanisms remain unclear. In a longitudinal observational study, we examined the relationship between smoking, transition to chronic pain, and brain physiology. In 160 subjects with subacute back pain (SBP: back pain lasting 4–12 weeks, and no prior back pain [BP] for at least 1 year) pain characteristics, smoking status, and brain functional properties were measured repeatedly over 1 year. Sixty‐eight completed the study, subdivided into recovering (SBPr, n = 31) and persisting (SBPp, n = 37), based on >20% decrease in BP over the year. Thirty‐two chronic back pain (CBP: duration > 5 years) and 35 healthy controls were similarly monitored. Smoking prevalence was higher in SBP and CBP but not related to intensity of BP. In SBP, smoking status at baseline was predictive of persistence of BP 1 year from symptom onset (differentiating SBPp and SBPr with 0.62 accuracy). Smoking status combined with affective properties of pain and medication use improved prediction accuracy (0.82). Mediation analysis indicated the prediction of BP persistence by smoking was largely due to synchrony of fMRI activity between two brain areas (nucleus accumbens and medial prefrontal cortex, NAc‐mPFC). In SBP or CBP who ceased smoking strength of NAc‐mPFC decreased from precessation to postcessation of smoking. We conclude that smoking increases risk of transitioning to CBP, an effect mediated by corticostriatal circuitry involved in addictive behavior and motivated learning. Hum Brain Mapp 36:683–694, 2015. © 2014 Wiley Periodicals, Inc.